Intraoperative myocardial infarction: Kounis syndrome provoked by latex allergy - Marcoux, Veronica (BMJ Publishing Group, 2013)
We report the case of a 43-year-old man with anaphylactic shock and concurrent ST-elevation myocardial infarction during a planned inguinal hernia surgery. This event occurred shortly after introduction of latex into the surgical field. Coronary angiography revealed a 70% occlusive lesion in the right coronary artery. Further discussion with the patient revealed a potential latex allergy. Skin prick testing showed marked sensitisation to latex. The patient was subsequently diagnosed with the type II variant of Kounis syndrome.